2008
DOI: 10.1002/aic.11451
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the enhanced performance of pulsed bioreactors by mechanistic modeling

Abstract: in Wiley InterScience (www.interscience.wiley.com).In this work, steady-state mass balance based models were applied to two UASB reactors and three UAF for a better understanding of the role of pulsation on the efficacy improvement. Models were defined taking into account the hydraulic behavior of each digester and the limiting mechanism of the overall process kinetics (mass transfer or biochemical reaction rate). The application of the model allows to identify that mass transfer was the controlling step in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…For example, Franco et al (2008) have demonstrated that mechanistic kinetic modeling can explain the enhanced performance of pulsed bioreactors. However, the mechanistic modeling of (bio-)chemical reactions in homogeneous and heterogeneous systems is still one of the most relevant and yet not satisfactorily solved tasks in process engineering (Berger et al, 2001).…”
Section: Mechanistic Modeling Of Enzyme Immobilizatesmentioning
confidence: 99%
“…For example, Franco et al (2008) have demonstrated that mechanistic kinetic modeling can explain the enhanced performance of pulsed bioreactors. However, the mechanistic modeling of (bio-)chemical reactions in homogeneous and heterogeneous systems is still one of the most relevant and yet not satisfactorily solved tasks in process engineering (Berger et al, 2001).…”
Section: Mechanistic Modeling Of Enzyme Immobilizatesmentioning
confidence: 99%
“…In another study, a steady state mechanistic model was applied to explain the role of pulsation on the performance enhancement for UASB and UAF (Franco et al, 2008). The model revealed that mass transfer was higher in pulsed reactors and thus mass transfer was a controlling step in all reactors.…”
Section: Fang and Govindmentioning
confidence: 99%